2010
DOI: 10.1097/pcc.0b013e3181b0630f
|View full text |Cite
|
Sign up to set email alerts
|

A prospective crossover comparison of neurally adjusted ventilatory assist and pressure-support ventilation in a pediatric and neonatal intensive care unit population*

Abstract: In a neonatal and pediatric intensive care unit population, ventilation in neurally adjusted ventilatory assist mode was associated with improved patient-ventilator synchrony and lower peak airway pressure when compared with pressure-support ventilation with a pneumatic trigger. Ventilating patients in this new mode seem to be safe and well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
88
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 32 publications
(27 reference statements)
11
88
2
Order By: Relevance
“…These results are in line with studies in adults that all reported similar synchrony improvement with NAVA (5,11,12,20,21). In the pediatric population, no study has yet quantified the trigger delays and cycling-off delays during conventional ventilation and during NAVA, although two feasibility studies have demonstrated that during NAVA, at least two-thirds of assisted breaths were triggered by the neural signal (17,18). A recent study in a heterogeneous pediatric population showed, similar to our findings, that the inspiratory and expiratory phases of the ventilator match the neural phases of the patient better during NAVA (91% of the time was synchronous) as compared with PCV or pressure-regulated volume-control mode (66% of the time was synchronous) (19).…”
Section: Nava In Infantssupporting
confidence: 75%
See 2 more Smart Citations
“…These results are in line with studies in adults that all reported similar synchrony improvement with NAVA (5,11,12,20,21). In the pediatric population, no study has yet quantified the trigger delays and cycling-off delays during conventional ventilation and during NAVA, although two feasibility studies have demonstrated that during NAVA, at least two-thirds of assisted breaths were triggered by the neural signal (17,18). A recent study in a heterogeneous pediatric population showed, similar to our findings, that the inspiratory and expiratory phases of the ventilator match the neural phases of the patient better during NAVA (91% of the time was synchronous) as compared with PCV or pressure-regulated volume-control mode (66% of the time was synchronous) (19).…”
Section: Nava In Infantssupporting
confidence: 75%
“…In studies comparing conventional ventilation to NAVA (and in those studies where the NAVA level was adjusted so that peak pressures were matched), most have reported lower mean airway pressure during NAVA (16,17,19,26). In our study, a trend for lower mean airway pressure was also observed, but it did not reach significance (P = 0.17), probably because of insufficient power (retrospectively calculated power at 28%).…”
Section: Nava In Infantscontrasting
confidence: 47%
See 1 more Smart Citation
“…Breatnach et al 34 compared NAVA to PSV in 16 ventilated infants and children (age range 2 d to 4 years, mean 9.7 months, weight range 2.4 -13.7 kg, mean 6.2 kg). NAVA improved patient-ventilator synchrony and lowered the peak inspiratory pressure, compared to PSV.…”
Section: Neurally Adjusted Ventilatory Assistmentioning
confidence: 99%
“…NAVA delivers mechanical assistance in proportion to patient effort, allowing the tailoring of the mechanical support to patient' respiratory characteristics. Several studies 15,[22][23][24][25][26] showed that NAVA is a safe and reliable mode in the pediatric and infant population. It improved synchrony and patient comfort, reduced ventilator drive, and increased breath-tobreath mechanical variability.…”
Section: Discussionmentioning
confidence: 99%